2015
DOI: 10.1097/aln.0000000000000511
|View full text |Cite
|
Sign up to set email alerts
|

Transfusion Requirements in Surgical Oncology Patients

Abstract: A liberal erythrocyte transfusion strategy with a hemoglobin trigger of 9 g/dl was associated with fewer major postoperative complications in patients having major cancer surgery compared with a restrictive strategy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
75
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 185 publications
(76 citation statements)
references
References 30 publications
1
75
0
Order By: Relevance
“…5,25 While blood transfusion can be lifesaving for patients experiencing profound anemia by increasing oxygen delivery capacity and tissue perfusion, 10,26 transfusion can result in diminished immune function and other transfusionrelated adverse events such as acute lung injury. 4,8,9,27,28 Although previous randomized clinical trials and recent guidelines suggest that red cell transfusion is usually not indicated above a Hb concentration of 7 or 8 g/dL in a hemodynamically stable patient, the ideal trigger for transfusion Of note, among patients who were transfused, the incidence of complications did increase slightly over the periods examined (P=0.03). Consistent with previous findings, 5,13,16,29-31 we noted that restrictive PRBC transfusion practices did not result in worse risk-adjusted perioperative outcomes compared with a liberal transfusion strategy.…”
Section: Discussionmentioning
confidence: 84%
See 4 more Smart Citations
“…5,25 While blood transfusion can be lifesaving for patients experiencing profound anemia by increasing oxygen delivery capacity and tissue perfusion, 10,26 transfusion can result in diminished immune function and other transfusionrelated adverse events such as acute lung injury. 4,8,9,27,28 Although previous randomized clinical trials and recent guidelines suggest that red cell transfusion is usually not indicated above a Hb concentration of 7 or 8 g/dL in a hemodynamically stable patient, the ideal trigger for transfusion Of note, among patients who were transfused, the incidence of complications did increase slightly over the periods examined (P=0.03). Consistent with previous findings, 5,13,16,29-31 we noted that restrictive PRBC transfusion practices did not result in worse risk-adjusted perioperative outcomes compared with a liberal transfusion strategy.…”
Section: Discussionmentioning
confidence: 84%
“…5 In contrast, a separate study by de Almeida et al demonstrated that patients undergoing abdominal cancer surgery who were transfused liberally had a lower absolute risk of overall complications compared patients transfused with a restrictive strategy. 4 The current study expanded on these previous studies as it examined a large cohort of patients (n>10,000) who underwent either a CT-V or complex GI surgical procedure. Importantly, we noted that the risk of postoperative complications following cardiothoracic, vascular, or complex general surgery cases was not associated with a more restrictive transfusion strategy on multivariable analysis.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations